2004
DOI: 10.1007/978-1-4020-2330-9_11
|View full text |Cite
|
Sign up to set email alerts
|

Some Desiderata for Liberal Supertrees

Abstract: Abstract:Although a variety of supertree methods has been proposed, our understanding of these methods is limited. In turn, this limits the potential for biologists who seek to construct supertrees to make informed choices among the available methods. In this chapter we distinguish between supertree methods that offer a conservative synthesis of the relationships that are agreed upon or uncontradicted by all the input trees and liberal supertree methods which have the potential to resolve conflict. We list a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…The performance of supertree building methods should meet a series of properties proposed by Steel et al () and Wilkinson et al (, ) in a mathematical and practical context, respectively. Overall, these properties specify that: (i) the taxa in the output supertree should be equal to those found in all source trees; (ii) that there should be a phylogenetic agreement between the relationships featured in the output supertree and the original source trees; and furthermore (iii) whenever there are scaffold source trees, the resulting supertree should display their structure; and (iv) the supertree method should be applicable to any set of source trees, regardless of the order they are fed into the algorithm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance of supertree building methods should meet a series of properties proposed by Steel et al () and Wilkinson et al (, ) in a mathematical and practical context, respectively. Overall, these properties specify that: (i) the taxa in the output supertree should be equal to those found in all source trees; (ii) that there should be a phylogenetic agreement between the relationships featured in the output supertree and the original source trees; and furthermore (iii) whenever there are scaffold source trees, the resulting supertree should display their structure; and (iv) the supertree method should be applicable to any set of source trees, regardless of the order they are fed into the algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…The design of algorithms for supertree construction is a very active field of research to the point where currently there are at least 20 supertree construction methods (Bininda‐Emonds, ; Bordewich et al, ; Ranwez et al, ; Bansal et al, ; Swenson et al, ). Since these methods perform differently (because of their inherent algorithmic diversity), Steel et al () and Wilkinson et al () suggested several properties that are desirable in supertree methods that can be summarized in three main points. First, there should be a close phylogenetic correspondence between the primary source trees and the resulting supertree.…”
mentioning
confidence: 99%
“…With this novel approach rogue taxa exist only when there is some 'reduced' consensus, i.e. a consensus of pruned trees, that, according to the RNR optimality criterion, is better than the corresponding plenary consensus, i.e., a consensus including all the leaves (Wilkinson, Thorley, Pisani, Lapointe, & McInerney, 2004 RNR has two alternative optimality criteria. The relative information content (Pattengale, Aberer, Swenson, Stamatakis, & Moret, 2011) is simply the degree of resolution of the consensus (i.e., the number of internal branches), maximization of which is also what Wilkinson (1995b) used to distinguish primary from other reduced consensus trees.…”
Section: Roguenarok (Rnr)mentioning
confidence: 99%
“…In recent contributions, Wilkinson et al. (2004, in press) have discussed the bias that asymmetric measures of fit introduce in supertree analysis.…”
mentioning
confidence: 99%